Early skeletal muscle deconditioning and reduced exercise capacity during (neo)adjuvant chemotherapy in patients with breast cancer - Mallard, Joris; Hucteau, Elyse; Schott, Roland; Trensz, Philippe; Pflumio, Carole; Kalish‐Weindling, Michal; Favret, Fabrice; Pivot, Xavier; Hureau, Thomas J.; Pagano, Allan F. (Cancer, 2023)
Background Fatigue is a hallmark of breast cancer and is associated with skeletal muscle deconditioning. If cancer‐related fatigue occurs early during chemotherapy (CT), the development of skeletal muscle deconditioning and its effect on exercise capacity remain unclear. The aim of this study was to investigate the evolution of skeletal muscle deconditioning and exercise capacity in patients with early‐stage breast cancer during CT. Methods Patients with breast cancer had a visit before undergoing CT, at 8 weeks, and at the end of chemotherapy (post‐CT). Body composition was determined through bioelectrical impedance analysis. Knee extensor, handgrip muscle force and fatigue was quantified by performing maximal voluntary isometric contractions and exercise capacity using the 6‐min walking test. Questionnaires were also administered to evaluate quality of life, cancer‐related fatigue, and physical activity level. Results Among the 100 patients, reductions were found in muscle mass (−2.3%, p = .002), exercise capacity (−6.7%, p < .001), and knee extensor force (−4.9%, p < .001) post‐CT, which occurred within the first 8 weeks of treatment with no further decrease thereafter. If muscle fatigue did not change, handgrip muscle force decreased post‐CT only (−2.5%, p = .001), and exercise capacity continued to decrease between 8 weeks and post‐CT (−4.6%, p < .001). Quality of life and cancer‐related fatigue were impaired after 8 weeks (p < .001) and remained stable thereafter, whereas the physical activity level remained stable during chemotherapy. Conclusions Similar to cancer‐related fatigue, skeletal muscle deconditioning and reduced exercise capacity occurred early during breast cancer CT. Thus, it appears essential to prevent these alterations through exercise training implemented during CT. Using measurements obtained before, during, and after chemotherapy in patients with early‐stage breast cancer, it is highlighted that skeletal muscle deconditioning and decrease in exercise capacity appeared early during the treatment. These findings support the significance of prescribing exercise training as supportive care during chemotherapy to prevent these harmful side effects.